Accelerated 3D echo‐planar imaging with compressed sensing for time‐resolved hyperpolarized 13C studies. Issue 2 (24th January 2016) - Geraghty, Benjamin J.; Lau, Justin Y.C.; Chen, Albert P.; Cunningham, Charles H.
Abstract : Purpose: To enable large field‐of‐view, time‐resolved volumetric coverage in hyperpolarized 13 C metabolic imaging by implementing a novel data acquisition and image reconstruction method based on the compressed sensing framework. Methods: A spectral‐spatial pulse for single‐resonance excitation followed by a symmetric echo‐planar imaging (EPI) readout was implemented for encoding a 72 × 18 cm 2 field of view at 5 × 5 mm 2 resolution. Random undersampling was achieved with blipped z‐gradients during the ramp portion of the echo‐planar imaging readout. The sequence and reconstruction were tested with phantom studies and consecutive in vivo hyperpolarized 13 C scans in rats. Retrospectively and prospectively undersampled data were compared on the basis of structural similarity in the reconstructed images and the quantification of the lactate‐to‐pyruvate ratio in rat kidneys. Results: No artifacts or loss of resolution are evident in the compressed sensing reconstructed images acquired with the proposed sequence. Structural similarity analysis indicate that compressed sensing reconstructions can accurately recover spatial features in the metabolic images evaluated. Conclusion: A novel z‐blip acquisition sequence for compressed sensing accelerated hyperpolarized 13 C 3D echo‐planar imaging was developed and demonstrated. The close agreement in lactate‐to‐pyruvate ratios from both retrospectively and prospectively undersampled data from rats shows that metabolic information is preserved with acceleration factors up to 3‐fold with the developed method. Magn Reson Med 77:538–546, 2017. © 2016 International Society for Magnetic Resonance in Medicine